THE DEVELOPMENT OF ARTIFICIAL INTELLIGENCE: GLOBAL CHANGES AND THE APPROACH OF THE INTERNATIONAL COMMUNITY - MEDETBAEVA, AKSUNGUL (YURIST AXBOROTNOMASI, 2025)
This article explores the transformative potential of artificial intelligence (AI) and the emerging challenges it brings to the modern world. AI today is reshaping important sectors such as healthcare, education, industry, and governance. In healthcare, it enables early diagnosis and personalized treatment; in education, it supports adaptive learning and digital innovation; in industry, it increases efficiency through automation; and in governance, it improves decision-making and public services. At the same time, AI raises serious ethical, legal, and social concerns. Issues such as privacy protection, algorithmic bias, responsibility for AI-driven decisions, and the risk of deepening social inequality require careful attention. Therefore, the development of AI must be guided by principles of responsibility, transparency, and humancentered values. This article employs descriptive-analytical and comparative-legal methods, drawing upon interdisciplinary sources in law, economics, and ethics. The article also emphasizes the global response to these challenges. International organizations, including the United Nations, the European Union, and UNESCO, are developing regulatory and ethical frameworks to ensure that AI contributes to sustainable and inclusive growth. Particular attention is given to Uzbekistan’s national strategies in this area. The country is actively investing in digital transformation, scientific research, and the training of specialists in AI technologies. The main goal of this article is to provide a balanced understanding of how AI progress can be guided through international cooperation and national initiatives, ensuring that artificial intelligence serves the interests of humanity and supports sustainable development.